Implications of slowing growth in emerging market economies for hunger and poverty in rural areas of developing countries - Laborde Debucquet, David; Martin, Will (International Food Policy Research Institute, 2016)
Over the past 25 years, economic growth rates in many developing countries have outpaced those in industrialized countries, and per capita incomes of these two groups of countries have started to converge. Growth in developing countries contributed to a dramatic drop—from 37 percent to 13 percent—in the global extreme poverty rate between 1990 and 201. However, the global economic outlook has deteriorated recently. This paper examines the impact of the actual and projected slowdown in the world economy since 2012 on the poor and on the potential for achievement of the Sustainable Development Goals (SDGs). It builds on the changes between 2012 and late 2015 in the International Monetary Fund’s World Economic Outlook projections to provide the basic slowdown scenario. It then uses a global model to assess the impacts of lower rates of productivity growth and consequent lower savings and investment on key price and income variables. The productivity shocks are passed directly to the production activities included in household microsimulation models for almost 300,000 households. These households are also affected by the modeled changes in prices and wages. Simulations allow us to assess the impacts of the slowdown on the real household incomes of the poor, and hence on the poverty rate. The results suggest that the poorest countries will see the greatest slowdown in poverty reduction, with over 5 percent of their population projected to remain below the poverty line. Overall 38 million fewer people will leave extreme poverty compared to earlier projections. Farm households are at particular risk in middle-income countries, with over 1.5 percent more of the farming population potentially not escaping extreme poverty in these countries. By 2030, average extreme poverty in rural areas is now projected to be about 7.5 percent, rather than 7.1 percent. While substantial poverty reduction is still expected between now and 2030, a strong focus on policies for poverty reduction will be vital to achieving the first SDG goal of eliminating poverty.